PENGARUH PERTUMBUHAN PENJUALAN, PROFITABILITAS, STRUKTUR AKTIVA DAN STRUKTUR KEPEMILIKAN TERHADAP STRUKTUR MODAL PADA PERUSAHAAN MANUFACTURE GO PUBLIC DI BURSA EFEK INDONESIA TAHUN 2008 â 2010 - Maskur, Maskur (Students Journal of Economic and Management, 2012)
Today the business world depends on all the funding issues, some experts agree that in order to get out of this economic crisis in the real sector should be mobilized to stimulate economic growth. However, many obstacles faced by the business, one of the most crucial is the problem of funding. The business world suffered a setback due to the credit crunch - credit given to the business regardless of the legal lending limit in the past by banks and credit worthiness issues approved. Therefore, both the management and the creditors are supposed to determine the factors associated with these funding issues. By knowing the factors that affect the capital structure is expected to be taken into consideration for management evaluation.